2005
DOI: 10.1002/chi.829
|View full text |Cite
|
Sign up to set email alerts
|

Building a stable workforce: recruitment and retention in the child care and early years sector

Abstract: The paper presents findings from research aimed at identifying effective approaches to the recruitment and retention of child care workers, conducted to assist the UK Government's Childcare Strategy. The paper explores the practices and views of child care employers, Early Years Development and Childcare Partnerships (EYDCPs) and child care workers in a range of settings (including day nurseries, playgroups and out-of-school care). Two key issues explored in the paper are the need for greater employer responsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
22
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 9 publications
5
22
1
1
Order By: Relevance
“…Nonetheless, these studies give some indications of the particular pressures experienced by male staff that may account for their reluctance to apply for jobs in ID services; notably questions about their motivation for undertaking this work and exposure to accusations of abuse. Rolfe, 2005) identified similar reasons for discouraging males' entry to childcare services where employment rates of males have fallen to less than 5% nationally. In nursing too, the number of male registered nurses in Britain is rarely over 10% of the total, although in the Netherlands it is higher (23%; Davies, 1995).…”
Section: Discussionmentioning
confidence: 98%
“…Nonetheless, these studies give some indications of the particular pressures experienced by male staff that may account for their reluctance to apply for jobs in ID services; notably questions about their motivation for undertaking this work and exposure to accusations of abuse. Rolfe, 2005) identified similar reasons for discouraging males' entry to childcare services where employment rates of males have fallen to less than 5% nationally. In nursing too, the number of male registered nurses in Britain is rarely over 10% of the total, although in the Netherlands it is higher (23%; Davies, 1995).…”
Section: Discussionmentioning
confidence: 98%
“…However, a number of major issues of both quantity and quality confront the achievement of these aims for the children’s workforce. There have been chronic problems in recruiting and retaining workers in a range of child care settings (Audit Commission 2002; Department for Education and Skills 2003; Rolfe 2005). The implications of these deficits are so serious that failure to analyse and address them will inevitably significantly undermine the laudable ambitions of the government.…”
Section: Introductionmentioning
confidence: 99%
“…Ideally, EC educators should be seen as consummate professionals who are recognized for the skills and knowledge they bring to the complexities of educative care work with young children (Cameron et al, 2002;Fenech et al, 2004;P. Moss, 2003;Rolfe, 2005). As such there is a need to move away from the continual auditing of key competencies for accountability, and to move towards a model of quality assurance that focuses on staff engaging in reflective practice and critical inquiry (Maloney & Barblett, 2002;Power, 2007).…”
mentioning
confidence: 99%
“…International studies have shown that retention rates of EC educators are lower than that of most other occupations (Colton and Roberts, 2007;Farrell and Rusbult, 1981;Gable et al, 2007;Rolfe, 2005;Whitebook and Sakai, 2003). The demand for LDC services is set to continue, however, for two key reasons.…”
mentioning
confidence: 99%